Penerapan Metode ADL Pengaruh Harga BBM dan Jumlah Uang Beredar terhadap Inflasi di Kota Medan - Sarah, Henny May; Siregar, Machrani Adi Putri; Widyasari, Rina (Universitas Cokroaminoto Palopo, 2024)
Inflation is a general and continuous tendency to increase the price of goods. Factors causing inflation include increases in fuel prices and money supply. The general impact of inflation is a decrease in domestic investment, an increase in interest rates, encouraging investment through speculation, failure to develop, economic instability, a balance of payments deficit, and lowering the standard of living and welfare of the community.The purpose of this study is to determine the effect of fuel prices and the amount of money in circulation on inflation in the city of Medan. The model used is the Autoregressive Distributed Lag (ADL) Model. If the variables in the ADL model, both the dependent variable and the independent variable have a unit root, usually performed stasionary test. The ADL model as-sumes stationary data even if the dependent and independent variables are nei-ther stationary or cointegrated. The test results indicate that there is no cointe-gration between the variables, and the model produced indicates that the varia-bles affecting the price of fuel and the availability of money have a considerable impact on inflation, with a coefficient of determination of 71,4% and a MAPE value of 15,64%, making it suitable for making predictions.